Englacial Warming Indicates Deep Crevassing in Bowdoin Glacier, Greenland - Seguinot, Julien; Funk, Martin; Bauder, Andreas; Wyder, Thomas; Senn, Cornelius; Sugiyama, Shin (Frontiers in Earth Science, 2020)
All around the margins of the Greenland Ice Sheet, marine-terminating glaciers have recently thinned and accelerated. The reduced basal friction has yielded increased flow velocity, while the rate of longitudinal stretching has been limited by ice viscosity, which itself critically depends on temperature. However, ice temperature has rarely been measured on such fast-flowing and heavily crevassed glaciers. Here, we present a three-year record of englacial temperatures obtained 2 (in 2014) to 1 km (in 2017) from the calving front of Bowdoin Glacier (Kangerluarsuup Sermia), a tidewater glacier in northwestern Greenland. Two boreholes separated by 165 (2014) to 197 m (2017) show significant temperature differences averaging 2.07 ∘C on their entire depth. Englacial warming of up to 0.39∘C a−1, an order of magnitude above the theoretical rate of heat diffusion and viscous dissipation, indicates a deep and local heat source within the tidewater glacier. We interpret the heat source as latent heat from meltwater refreezing in crevasses reaching to, or near to, the bed of the glacier, whose localisation may be controlled by preferential meltwater infiltration in topographic dips between ogives.